(untitled) (Práxis Educativa, 2020)
The homeschooling movement has produced a discourse to support the idea of effectiveness of home schooling. Dissonant of this narrative, the voice of the educators echoes reaffirming the indispensability of the school, the teacher and the State as providers of the right to education for learning and the full development of children and adolescents. In view of the defense that reverberates in the impossibility of an effective reaction from the subjects of this education (the students), this paper aims to highlight the implications of homeschooling for schooling, teacher professionalization and for education as a right. It uses discourse analysis, based on Fairclough, in a bibliographic-documentary study. The results indicate that the advocacy of homeschooling is supported in particular and exogenous cases without scientific evidence and disregards the risks of student segregation from the social learning environment. Keywords: Right to education. Homeschooling. Teaching professionalization.